If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 29 + -2x + 4 = -4x Reorder the terms: 29 + 4 + 3x + -2x = -4x Combine like terms: 29 + 4 = 33 33 + 3x + -2x = -4x Combine like terms: 3x + -2x = 1x 33 + 1x = -4x Solving 33 + 1x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 33 + 1x + 4x = -4x + 4x Combine like terms: 1x + 4x = 5x 33 + 5x = -4x + 4x Combine like terms: -4x + 4x = 0 33 + 5x = 0 Add '-33' to each side of the equation. 33 + -33 + 5x = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 5x = 0 + -33 5x = 0 + -33 Combine like terms: 0 + -33 = -33 5x = -33 Divide each side by '5'. x = -6.6 Simplifying x = -6.6
| 2000+9=1000 | | 12ab^2+4ab-16a^3b^2= | | 6(1+6x)=-102 | | -4(u+5)+3u= | | 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 | | 4x+6=-2x-6 | | 14y^2-12y+3=0 | | e^2x=-4x |